Probabilistic Evaluation of a Power System’s Reliability and Quality Measures - Alshammari, B. M. (Engineering, Technology & Applied Science Research, 2020)
Reliability and performance quality measures computed so far are deterministic in nature. They represent one operating state (a snapshot of the system conditions) in which the required demand and generation and transmission capacities are known with 100% certainty. In this paper, a general and coherent formulation is presented, which can be used to account for the randomness associated with the load level as well as the availability of generation and transmission capacities. The general probability formulation can be used to calculate various reliability indices and quality measures. The paper describes the new approach for computing probabilistic evaluation (expected value) of the reliability indices and performance quality measures and presents illustrative applications. The methodology used in this paper constitutes a new line of research in the probabilistic reliability evaluation of a system where the derived system-wide performance quality indices are capable of classifying and exhibitionistic areas of deficiencies, bottlenecks and redundancies in large-scale power grids.